Kajian Perubahan Curah Hujan Terhadap Sumber Daya Air Minum Di Desa Nano Kecamatan Boking Kabupaten Timor Tengah Selatan - Ira Semaya Nenometa; Mikael Samin; Arfita Rahmawati (Geosfera: Jurnal Penelitian Geografi, 2025)
Changes in rainfall are one of the factors that affect spring discharge, where during the dry season the spring discharge decreases and during the rainy season the spring discharge will increase. This study aims to (1) Determine the value of rainfall intensity in Nano Village, Boking District, South Central Timor Regency (2) Determine the distribution of rainfall in Nano Village, Boking District, South Central Timor Regency (3) Determine the relationship between changes in rainfall and drinking water resources in Nano Village, Boking District, South Central Timor Regency. The method used in this study is a quantitative method. Rainfall data for 2020–2024 was obtained from three rain posts, (1) to answer the first and second objectives, the data was analyzed using the methodPoligon Thiessen, (2) to answer the third objective, the data was analyzed using Pearson correlation..The results of the study indicate that the rainfall intensity value in Nano Village is categorized as light rain, while the distribution of rainfall in Nano Village is categorized as a monsoonal pattern. The relationship between rainfall and drinking water resources shows a positive relationship where high rainfall increases spring discharge, conversely, when rainfall decreases, groundwater supply decreases and spring discharge decreases. The conclusion of this study is that rainfall has a significant influence on the availability of drinking water resources, especially in springs. In the rainy season, increased rainfall causes increased water infiltration into the ground so that groundwater reserves increase and have an impact on increasing spring discharge. Conversely, in the dry season, low rainfall reduces the groundwater recharge process, so that spring discharge decreases.